Pengembangan Instrumen Asesmen Higher Order Thinking Skills (Hots) Dalam Pembelajaran Fisika Pada Materi Hukum Newton Kelas X SMA/ MA - phito, veldry; arief, asmaiwaty; roza, media (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
This research is motivated by the use of cognitive assessment instruments on daily and mid-semester tests on learning class X physics used in the form of questions that tend to test more aspects of memory, understanding and application. While questions that test aspects of analysis, evaluation and creation are not widely available. In the matter of Newton's law, most students still experience difficulties in solving problems related to Newton's law. In fact, the questions on Newton's law are related to the application of technology in everyday life. To overcome these problems the students need to be directed to develop high-level thinking skills. Therefore, one way to improve students' high-level thinking skills by carrying out HOTS-based evaluations. In line with these problems it is necessary to feel it. Development of Higher Order Thinking Skills (HOTS) Assessment Instruments in Physics Learning in Newton's Legal Material Class X SMA / MA. The purpose of this study is to produce Higher Order Thinking Skills (HOTS) Assessment Instruments in Physics Learning in Newton's Law Material of Class X SMA / MA which is valid, practical and effective